The effect of a therapeutic program based on strengthening exercises centered on the lower back muscles on the severity of pain and quality of life among young subjects - ضويا, رشا (Latakia University Journal -Medical Sciences Series, 2024)
The research aimed to examine the effect of a therapeutic training program and its impact on the severity of pain and quality of life among young peoples, in addition to identifying the correlation between the intensity of pain and quality of life among these subjects. The study used Brief Pain Inventory Short Form questionnaire, as using the short version of the BPI allows us to identify painful areas in the research sample and the effect of pain on activities of daily life in addition to its intensity while answering the questionnaire and in the previous week. The question of pain relief through medications also allows us to exclude the participant who takes medications to relieve perceived pain so that it does not affect the measurements in the experiment. The study also applied a therapeutic program of strengthen exercises concentrated on lower back for a period of 8 weeks, at a rate of 3 hours of training per week. The duration of the training session is (45 minutes) divided into (4) parts (warm-up - stretching exercises - strength exercises - calm-down exercises). The subjects includes 10 young adults aged between 21-25 years. The results of the study led to the fact that strengthen exercises concentrated on the lower back muscles contributed significantly to a decrease in the intensity of pain and increase the quality of life. The statistical results also demonstrated that there was a negative correlation between pain scores and the level of quality of life.